Chronic traumatic encephalopathy research viewed in the public domain: What makes headlines?. (20th March 2020) - Wolfson, Daniel I.; Kuhn, Andrew W.; Kerr, Zachary Y.; Brett, Benjamin L.; Yengo-Kahn, Aaron M.; Solomon, Gary S.; Zuckerman, Scott L.
ABSTRACT: Objective : To determine chronic traumatic encephalopathy (CTE)-related publication characteristics associated with higher Altmetric scores. Methods : A systematic review of the CTE literature was conducted using PubMed. Publications were coded for: journal impact factor (JIF); publication type (primary versus non-primary data collection); discussion of American football; contact sport-CTE association conclusion (yes versus no/neutral); and Altmetric score. Multivariable ordinal logistic regression identified predictors of higher Altmetric scores. Results : Most of the 270 CTE-related publications did not include primary data collection (60%). The median Altmetric score was 12 (range = 0–3745). Higher Altmetric scores were associated with primary data collection [Odds ratio (OR)Adjusted  = 2.29; 95% confidence interval (CI) = 1.35–3.89] and discussing American football (ORAdjusted  = 2.11; 95%CI = 1.24–3.59). Among publications concluding contact sport-CTE associations, higher Altmetric scores were associated with higher JIF (3-point-JIF-increase ORAdjusted = 2.11; 95%CI = 1.24–3.59); however, the association of higher Altmetric scores with higher JIF was not found among neutral publications or those concluding no contact sport-CTE associations (3-point-JIF-increase ORAdjusted  = 1.07; 95%CI = 0.94–1.22). Conclusions : Most CTE-related publications (60%) did not involve primary data collection. Publication characteristics such as higher JIF and concluding contact sport-CTE associations were associated with higher Altmetric scores. It is important for the academic community to consider strategies to counter publication and promotion bias in the presentation of CTE literature.